A simple and rapid method to differentiate Arthroderma benhamiae from Microsporum canis. (29th November 2012) - Mayser, Peter; Budihardja, Debby
Summary Background: Arthroderma benhamiae is increasingly isolated in Central Europe. In culture, this dermatophyte is difficult to differentiate macroscopically from Microsporum canis, which is microscopically also true for weak or non‐sporulating strains. Although there are valid molecular methods for differentiating between these two dermatophytes, in everyday practice it would be helpful for epidemiological and treatment considerations to have a simple and rapid method available for discrimination. Methods: Five commercially available chromogenic agar media were incubated with culture material of M. canis and A. benhamiae of different ages (2–21 days). Their color was evaluated at different temperatures (4, 20, 25, and 30 ∞C) and for different incubation periods (2 hours – 7 days). Results: Under the selected conditions, Candi‐SelectTM 4 was most suitable. All M. canis strains tested (n = 21) showed a pink or purple coloration of the agar, while 5 out of 6 A. benhamiae strains (n = 30) showed a turquoise coloration. The best results were achieved with an incubation temperature of 25 ∞C and small inocula derived from primary cultures. Results could be evaluated after 2–4 hours. Conclusions: In addition to searching for the origin of infection (in A. benhamiae almost exclusively guinea pigs, and for M. canis dogs and cats), distinguishing between the Trichophyton and Microsporum genera is most important, especially for the selection of a systemic antimycotic agent in the treatment of tinea capitis in children. In the case of M. canis terbinafine is not the first choice, but rather griseofulvin, fluconazole or itraconazole. We present a method of differentiation using Candi‐SelectTM 4. When done with a primary culture, this allows for presumptive identification within a few hours and thus prompt initiation of pathogen‐specific therapy.